Vigencia de la «banda típica» de la provincia de Chumbivilcas, departamento de Cuzco, Perú - Cárdenas Coavoy, Hubert Ramiro (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This text is an ethnographic and sound approach to the «banda típica» (traditional band), one of the traditional musical groups with the greatest presence in the festivities of the districts and peasant communities of the province of Chumbivilcas, department of Cuzco, Peru. It is a descriptive work that examines the places where the band participates, the manner of dressing of its members, its instrumental composition and organization, the subject of the musical themes they interpret and their characteristic toques, exemplified by sound files recorded during field work and stored on the Internet to accompany this article.The field work began in March 2015 and gathers information obtained through participant observation, informal conversations, as well as individual and group interviews with traditional and popular musicians in the framework of the anniversary of the province of Chumbivilcas, (June 21, district de Santo Tomás); festivity of the of the Virgin of the Nativity, (September 8, district of Santo Tomás) and festivity of the of the Señor Justo Juez de Patapampa, (day of «compadres”, peasant community of Pfuisa, district of Llusco). Among the main findings is that the typical band has managed to adapt to the vertiginous changes of time due to the close link that it keeps with the turupukllay or «game of bulls», custom that is celebrated in the main festivities of the province of Chumbivilcas.

El presente texto es una aproximación etnográfica y sonora a la «banda típica», una de las agrupaciones musicales tradicionales con mayor presencia en las festividades de los distritos y comunidades campesinas de la provincia de Chumbivilcas, departamento de Cuzco, Perú. Se trata de un trabajo descriptivo que examina los lugares donde participa la banda, la manera de vestir de sus integrantes, su conformación instrumental y organización, la materia de los temas musicales que interpretan y sus toques característicos, ejemplificados con archivos sonoros registrados durante el trabajo de campo y almacenados en internet para acompañar este artículo. El trabajo de campo se inició en marzo de 2015 y recaba información obtenida mediante observación participante, conversaciones informales, así como entrevistas individuales y grupales efectuadas a músicos tradicionales y populares en el marco del aniversario de la provincia de Chumbivilcas (21 de junio, distrito de Santo Tomás); de la fiesta patronal de la Virgen de la Natividad (8 de setiembre, distrito de Santo Tomás) y de la fiesta patronal del Señor Justo Juez de Patapampa (día de «compadres», comunidad campesina de Pfuisa, distrito de Llusco). Entre los principales hallazgos se observa que la banda típica ha logrado adaptarse a los vertiginosos cambios del tiempo debido a la estrecha ligazón que guarda con el turupukllay o juego de los toros, celebrado en las principales festividades de la provincia de Chumbivilcas.
An overview of the «banda típica» (traditional band) of the province of Chumbivilcas, department of Cuzco, Peru
Keywords: Música tradicional; Banda típica; Banda militar; Chumbivilcas; Cuzco; https://purl.org/pe-repo/ocde/ford#5.04.03